- ASPEK HUKUM PEMBAGIAN WARIS ALM. SAMIR MENURUT HUKUM WARIS ISLAM INDONESIA - Ni Made Ananda Puteri Maharani; Bakri, Khairani (Reformasi Hukum Trisakti, 2023)
The transfer of property from the right of the heir to the heir is known as inheritance. When inheritance is divided, it causes issues in society. Problem statement: Whether or not Ruling No. 519/Pdt. G/2019/PA.TR complies with Indonesian Islamic Inheritance Law with regard to the legal features of Alm. Samir bin Haji Sain's inheritance distribution under Indonesian Islamic Law. The research method used normative research to examine the fundamentals of Islamic inheritance law. Descriptive research methodology is used. Secondary data sources are consulted in this study. The findings of this investigation and discussion relate to legal facets of inheritance distribution for the deceased. Samir Bin Haji Sain includes the following in accordance with Indonesian Islamic Inheritance Law: Samir Bin Haji Sain includes the share of siblings, more than one wife and the obligatory will and the suitability of Decision Number 519/Pdt. G/2019/PA.TR with Indonesian Islamic Inheritance Law, including determining siblings to inherit, determining the share of 2 wives and children out of wedlock. The conclusion of this article: the legal aspects involved in this case: the part of the brother, the obligatory will, the share of more than one wife. Decision no 519/Pdt. G/2019/PA.TR judges are not in accordance with Indonesian Islamic inheritance law, which originates from the Al-Qur'an, Hadith and Presidential Instruction (Inpres) Number 1 of 1991 concerning Compilation of Islamic Law.